Leishmania major cause of a cutaneous leishmaniasis in a car driver from East Azerbaijan province - Mahdi Parsaei; Shalaleh Ganji; Majid Khanmohammadi (مجله پزشکی دانشگاه علوم پزشکی تبریز, 2021)
Leishmaniasis is a zoonotic disease and is known as a health problem in all of the world. The patient, a 47-year-old man car driver from the city of Bostan Abad, with a history of traveling to cutaneous leishmaniasis endemic provinces last year, was referred to the city health center with a 17 mm, no discharge and pus with a necrotic appearance skin lesion. Biochemical, hematological parameters and urine culture and analysis were normal. Three smears were prepared with sterile vaccinostyle from the margins of the wound and transferred to a specific medium in sterile conditions. After staining the prepared smears from the wound, amastigotes with a large nucleus and small kinetoplast in macrophages and active promastigotes in the liquid phase of the medium were observed. Polymerase chain reaction (PCR) was performed using ITS-1 by specific primers. In the PCR product electrophoresis was compared with the marker bands and 350 bp band weight determined. With electrophoretic patterns and comparison with positive control band, isolates parasites belonged to the Leishmania genus. In order to definitively diagnose the parasite species, a sequencing method was used. The results showed 99% homology with Leishmania major. Finally, the patient with a diagnosis of rural cutaneous leishmaniasis was induction with Glucantime drug. Diagnosis of suspected cases with cutaneous leishmaniasis is of major importance. If an infected patient is diagnosed in the early stages of the disease, the extension of the scar after recovery, as well as the possible complications of rural infection can be prevented